2011
DOI: 10.1002/joc.2418
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Indian summer monsoon rainfall variability with the geophysical parameters over the Arctic region

Abstract: A study is carried out to understand whether the Indian summer monsoon rainfall variability is associated with the geophysical parameters over the Arctic region. The correlation analyses of the satellite-derived sea ice data for 29 years indicate that out of 9 sectors of the Arctic region, the Kara and Barents Seas sector's Sea Ice Extent (KBS SIE) during October has a strong relationship with the All-India Summer Monsoon Rainfall (AISMR) in the following year. This relationship is more pronounced for the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Previous studies have suggested about forcings, other than El Niño Southern Oscillation (ENSO), influencing the inter-annual variability of ISMR like Arctic seaice (Amita et al 2012), winter climate anomalies over Europe (Rajeevan 2002;Pai 2004), Atlantic SST (Srivastava et al 2002;Goswami et al 2006) and Eurasian snow cover (e.g. Hahn and Shukla 1976;Bamzai and Kinter 1997;Kripalani and Kulkarni 1999) since it was first put forward by Blanford (1884).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested about forcings, other than El Niño Southern Oscillation (ENSO), influencing the inter-annual variability of ISMR like Arctic seaice (Amita et al 2012), winter climate anomalies over Europe (Rajeevan 2002;Pai 2004), Atlantic SST (Srivastava et al 2002;Goswami et al 2006) and Eurasian snow cover (e.g. Hahn and Shukla 1976;Bamzai and Kinter 1997;Kripalani and Kulkarni 1999) since it was first put forward by Blanford (1884).…”
Section: Introductionmentioning
confidence: 99%
“…The significant relationship between cluster time series in Arctic region and ISMR show spatial and temporal variability in positive and negative ESI-tendency [34].…”
Section: Discussionmentioning
confidence: 90%
“…During negative ESI tendency, strong winds around the North Pole confine the cold Arctic air mass to the Arctic region causing surface cooling over this region, which is associated with above‐normal rainfall activity over India (Prabhu et al , ). Moreover, SO also restores positive phase before the beginning of monsoon, which is indicative of increased Indian rainfall activity.…”
Section: Resultsmentioning
confidence: 99%
“…During negative ESI tendency, eight independent cluster parameters are selected by cross-validation procedure, which show the least error in predicting the ISMR on the independent data set (RMSE = 5.83). During negative ESI tendency, strong winds around the North Pole confine the cold Arctic air mass to the Arctic region causing surface cooling over this region, which is associated with above-normal rainfall activity over India (Prabhu et al, 2012). Moreover, SO also restores positive phase before the beginning of monsoon, which is indicative of increased Indian rainfall activity.…”
Section: Linear and Non-linear Relationship Between Cluster Parametermentioning
confidence: 99%